2018
DOI: 10.3389/fpls.2018.00862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heavy Metals (Ni, Cu, and Zn) on Nitro-Oxidative Stress Responses, Proteome Regulation and Allergen Production in Basil (Ocimum basilicum L.) Plants

Abstract: One of the most significant biosphere contamination problems worldwide is derived from heavy metals. Heavy metals can be highly reactive and toxic according to their oxidation levels. Their toxic effects are associated with the increased production of reactive oxygen species (ROS) and cellular damage induced in plants. The present study focuses on the effects of nickel (Ni), copper (Cu), and zinc (Zn) applied to the soil on the antioxidant response and allergen production in the aromatic plant basil (Ocimum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(52 citation statements)
references
References 81 publications
6
34
0
Order By: Relevance
“…All this causes the production of extremely reactive hydroxyl radicals to be inhibited, so cell-building molecules are protected against oxidation (Pilon et al 2011). In the present study, increased SOD activity was found in two metallicolous ecotypes, similar to the effect of Ni 2+ or Cu 2+ on basil plants under controlled metal treatment (Georgiadou et al 2018). The SOD activity seems to be strongly correlated with the dose of metal in the growth medium and/or with the plant species as observed within Alyssum genus in the hyperaccumulating plants of A. argenteum and A. maritimum treated with Ni or Cd ions (Schickler and Caspi 1999).…”
Section: Antioxidant Response Of Tested Ecotypessupporting
confidence: 83%
“…All this causes the production of extremely reactive hydroxyl radicals to be inhibited, so cell-building molecules are protected against oxidation (Pilon et al 2011). In the present study, increased SOD activity was found in two metallicolous ecotypes, similar to the effect of Ni 2+ or Cu 2+ on basil plants under controlled metal treatment (Georgiadou et al 2018). The SOD activity seems to be strongly correlated with the dose of metal in the growth medium and/or with the plant species as observed within Alyssum genus in the hyperaccumulating plants of A. argenteum and A. maritimum treated with Ni or Cd ions (Schickler and Caspi 1999).…”
Section: Antioxidant Response Of Tested Ecotypessupporting
confidence: 83%
“…Similar to our results it was reported that increasing concentrations of Cu treatments resulted in a reduction of total protein concentration and Cu stressed had the most detrimental effects while Ni stress showed less damaging in Ocimum basilicum L. following a combined, biochemical, analytical, and physiological approach (Georgiadou et al, 2018). In another research, it was observed that APX, POD, and SOD were shown remarkable induction with the treatment of Cd, Cu (10, 20 and 50 ppm) in the leaves of tomato when compared to control group (Kısa, 2017).…”
Section: Peroxidase Activity Resultssupporting
confidence: 91%
“…Nickel, at an extremely low concentration (0.05 mM), enhances the activity of POD, SOD, and guaiacol peroxidase (GOPX) [20]. However, at elevated Ni concentrations (500 mg kg −1 ), antioxidative enzyme activity decreases and leads to oxidative damage in plants [21].…”
Section: Introductionmentioning
confidence: 99%